PENGARUH KECEMASAN MAHASISWA MATEMATIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA SOAL MATEMATIKA SMA ika SMA - Amelia, Anisa; Lestari, Ananda Maya; Surati, Iis (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The influence of mathematics student anxiety is not only seen from fear but also from the ability to solve problems. This research survey was conducted to ascertain whether there are consequences of math students' anxiety with problem solving abilities in high school math problems. The research method used in the research survey is quantitative research. Researchers collected data using questionnaires and tests. The data analysis technique uses a simple regression analysis technique assisted by SPSS 16. Based on the results of the analysis of the R square residual model, the effect of anxiety on problem solving is 29.5%, and the remaining 70.5% is caused by unimportant variables. Then based on the results of the ANOVA test the significant value (0.002) 0.05 (the value of the confidence level). So it can be concluded that there was an impact between the influence of anxiety and problem solving in high school math problems.